If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6x + -9 = 4x + 4 + -9 Reorder the terms: -9 + 2x + -6x = 4x + 4 + -9 Combine like terms: 2x + -6x = -4x -9 + -4x = 4x + 4 + -9 Reorder the terms: -9 + -4x = 4 + -9 + 4x Combine like terms: 4 + -9 = -5 -9 + -4x = -5 + 4x Solving -9 + -4x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + -4x + -4x = -5 + 4x + -4x Combine like terms: -4x + -4x = -8x -9 + -8x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -9 + -8x = -5 + 0 -9 + -8x = -5 Add '9' to each side of the equation. -9 + 9 + -8x = -5 + 9 Combine like terms: -9 + 9 = 0 0 + -8x = -5 + 9 -8x = -5 + 9 Combine like terms: -5 + 9 = 4 -8x = 4 Divide each side by '-8'. x = -0.5 Simplifying x = -0.5
| 16=-3m-5m | | 5(-5.5)-8=3+7(-5.5) | | -1+6v=-4v+3(3v-2) | | -4(n+6)=-4 | | 5x+44-7x=5+x-13 | | 3(b)=30 | | 7x+11=10x-26 | | y-(-2)=-1.333x-6 | | 9(0+7)-7= | | 6y=66-24x | | -3k=9(k-4) | | y-(-2)=-1.333-6 | | (2y-5)(6-3y)= | | 8-c=2 | | (2x+3)(2x+3.25)-9.75=15 | | 9(x+7)-7=56 | | 3a-4=a-14 | | 6(g)=36 | | 2x+3=y+2 | | 3(x-3)=8 | | -m=6(m+7) | | 3+f=12 | | (7x)=(5x+18) | | 3/4(6)= | | 50=2x-2+x+2x-2+x | | 1.5y=60-4x | | 20=-3(m-4)+11 | | 4x-20=-42 | | 5-6=-11+2x | | -9x-1=18 | | 95y=64x | | 14=-2(m-1)+6 |